A Hierarchically Organized Photoelectrode Architecture for Highly Efficient CdS/CdSe‐Sensitized Solar Cells. Issue 3 (23rd September 2013) - Park, Jong Hoon; Kim, Dong Hoe; Shin, Seong Sik; Han, Hyun Soo; Lee, Myeong Hwan; Jung, Hyun Suk; Noh, Jun Hong; Hong, Kug Sun
<x xml:space="preserve">Abstract</x> A form of photoelectrode architecture suitable for inorganic semiconductor solar cells is reported. The developed architecture consists of hierarchically organized TiO2 nanostructures with several tens of nanometer‐sized particles that have a large surface area and open channels with several hundred‐nanometer‐gaps perpendicular to the substrate. These are tailored by controlling the kinetic energy of the ablated species during pulsed laser deposition (PLD). To fabricate the solar cells, CdS and CdSe inorganic sensitizers are assembled onto the architecture by successive ionic layer adsorption and reaction and polysulfide solution is used as an electrolyte with lead sulfide counter‐electrodes. The inorganic semiconductor solar cells using the developed architecture (PLD‐TiO2) show high energy conversion efficiencies of 5.57% compared to a conventional mesoporous TiO2 film(NP‐TiO2) (3.84%) with an optical mask at 1 sun of illumination. The improved cell performance of PLD‐TiO2 is attributed to greater light‐harvesting ability, which results in the enhancement of the Jsc value. PLD‐TiO2 absorbs more CdS/CdSe because of its larger surface area and excellent adhesion properties with fluorine‐doped tin oxide (FTO) substrates. Additionally, due to its unique channel‐shaped architecture, PLD‐TiO2 has a longer electron lifetime compared to NP‐TiO2.